2018
DOI: 10.1016/j.cag.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

A task-and-technique centered survey on visual analytics for deep learning model engineering

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 73 publications
(188 reference statements)
0
44
0
Order By: Relevance
“…In addition, 3 out of the 7 survey papers made a general search on the web. Garcia et al 32 and Liu et al 28 found papers by checking the references of other publications, which makes it hard to assess the systematization of their process objectively. In addition, 3 out of these 7 survey papers searched for specific keywords, such as deep neural networks (DNNs), which also inspired our own methodology.…”
Section: General Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, 3 out of the 7 survey papers made a general search on the web. Garcia et al 32 and Liu et al 28 found papers by checking the references of other publications, which makes it hard to assess the systematization of their process objectively. In addition, 3 out of these 7 survey papers searched for specific keywords, such as deep neural networks (DNNs), which also inspired our own methodology.…”
Section: General Overviewmentioning
confidence: 99%
“…Endert et al 27 Garcia et al 32 Hohman et al 20 Liu et al 28 Lu et al 35 Sacha et al 36 Only those surveys that contained an explicit methodology are included. 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 ML: machine learning.…”
Section: Search Targets Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Explanatory techniques in this class aim to shed light upon the roles of various layers, units, and connections during both training and inference, and therefore both understand how and what the network has learned, and how to improve this process. A recent survey of techniques in this class is given in [49].…”
Section: Architecture-centric Techniquesmentioning
confidence: 99%